Islamic Human Rights in Palestine: Navigating the Challenges of the Israeli-Palestinian Conflict in the Era of Technological Advancements (5.0) - Fitri, Remeiliza (Golden Ratio of Data in Summary, 2025)
The Israeli-Palestinian conflict continues to pose profound challenges to the protection and promotion of human rights, particularly within the framework of Islamic principles. This study explores the intersection of Islamic human rights, technological advancements, and the ongoing conflict in Palestine, emphasizing how emerging technologies shape narratives, surveillance systems, and propaganda mechanisms that affect the Palestinian population. As the world transitions into the era of technological advancement (5.0), digital innovation increasingly influences warfare, media representation, and the enforcement of humanitarian principles. Within this context, the study examines how Islamic human rights concepts—such as justice (adl), equality, and human dignity (karamah insaniyah)—are tested and reinterpreted under occupation and conflict conditions. Employing a mixed-methods approach that integrates qualitative analysis of Islamic legal literature, international law, and human rights reports with quantitative data on technological impacts, this research highlights how technology both exacerbates and mitigates human rights violations. It further analyzes the role of international and non-governmental organizations in advocating for justice and accountability while navigating geopolitical constraints. Findings reveal that technological progress can either strengthen surveillance and control or, conversely, empower global awareness and advocacy for Palestinian rights. Ultimately, this study underscores the need to align digital ethics, Islamic human rights, and international legal frameworks to promote justice and human dignity in Palestine amid the transformative realities of the technological era.